(Meth)acrylic polymer, method for producing same, and resin composition
The development of a (meth)acrylic polymer with a low glass transition temperature, specific terminal structure, and crosslinkable functional groups addresses the issues of coloring and weather resistance in conventional RAFT method polymers, resulting in a polymer with enhanced weather resistance and low coloring.
Patent Information
- Application Number
- JP2020214275
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-12-23
AI Technical Summary
Conventional (meth)acrylic polymers obtained by RAFT method suffer from coloring issues due to sulfur-containing structures, and they exhibit insufficient weather resistance when used in outdoor applications.
A (meth)acrylic polymer with a glass transition temperature of -15° C. or less, featuring a specific terminal structure and a Hazen unit color number of 600 or less, is developed. This polymer can be a block copolymer with crosslinkable functional groups and structural units derived from (meth)acrylic acid alkyl ester compounds with alkyl groups of 10 or more carbon atoms.
The resulting (meth)acrylic polymer achieves high weather resistance and low coloring, making it suitable for applications such as sealing materials and tile adhesives.
Smart Images

Figure 0007661696000001 
Figure 0007661696000002 
Figure 0007661696000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a (meth)acrylic polymer, a method for producing the same, and a resin composition. [Background technology]
[0002] Known living radical polymerization methods include reversible addition-fragmentation chain transfer polymerization (RAFT), nitroxy radical (NMP), atom transfer radical polymerization (ATRP), polymerization using organotellurium compounds (TERP), polymerization using organoantimony compounds (SBRP), polymerization using organobismuth compounds (BIRP), and iodine transfer polymerization. Among these, the RAFT, NMP, and ATRP methods are industrially used from the viewpoints of polymerization controllability and ease of implementation. In particular, the RAFT method is attracting attention as a metal-free polymerization method that can be applied to the widest range of vinyl monomers.
[0003] (Meth)acrylic polymers obtained by the RAFT method (hereinafter also referred to as "RAFT polymers") may have a problem of coloration due to the sulfur-containing structure derived from the RAFT agent. Thus, it has been considered to remove the sulfur-containing structure derived from the RAFT agent from the RAFT polymer by subjecting the RAFT polymer to post-treatment (see, for example, Patent Documents 1 and 2).
[0004] Patent Document 1 discloses that sponge nickel is brought into contact with a RAFT polymer to replace the sulfur-containing structure of the RAFT polymer with a hydrogen atom, thereby obtaining a (meth)acrylic polymer from which the sulfur-containing structure has been removed. Patent Document 2 discloses that a RAFT polymer is treated with an azo compound or a peroxide to obtain a (meth)acrylic polymer from which the sulfur-containing structure derived from the RAFT agent has been removed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-197649 A [Patent Document 2] International Publication No. 2011 / 093401 Summary of the Invention [Problem to be solved by the invention]
[0006] In applications requiring colorless transparency, further improvements are required to further reduce coloration of (meth)acrylic polymers. In addition, according to the studies of the present inventors, conventional (meth)acrylic polymers that have been subjected to post-treatment to remove sulfur-containing structures derived from RAFT agents sometimes have insufficient weather resistance when used, for example, in outdoor applications. Particularly in recent years, high weather resistance and low coloration are required in the fields of sealing materials, tile adhesives, and the like.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a (meth)acrylic polymer that exhibits high weather resistance and low coloration. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and have found that by making the terminal structure of a (meth)acrylic polymer obtained by a RAFT method a specific structure and by making the glass transition temperature (Tg) within a specific range, it is possible to obtain a (meth)acrylic polymer in which coloring is sufficiently suppressed and which has excellent weather resistance, and have completed the present invention. Specifically, the present invention provides the following means.
[0009] [1] A (meth)acrylic polymer having a glass transition temperature of -15°C or lower, at least one terminal structure in a molecular chain being a structure represented by the following formula (1), and having a Hazen color unit number (APHA) of 600 or less. [ka] (In formula (1), R represents a residue obtained by removing an acryloyloxy group from an acrylic ester compound contained in the monomer that constitutes the molecular chain.)
[0010] [2] The (meth)acrylic polymer according to [1] above, which has a crosslinkable functional group. [3] The (meth)acrylic polymer according to [1] or [2] above, which is a block copolymer having two or more polymer blocks. [4] The (meth)acrylic polymer according to any one of the above [1] to [3], which contains a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms. [5] The (meth)acrylic polymer according to any one of the above [1] to [4], having a molecular weight distribution (Mw / Mn) of 2.5 or less.
[0011] [6] A resin composition comprising the (meth)acrylic polymer according to any one of the above [1] to [5]. [7] The resin composition according to [6], further comprising a polyoxyalkylene polymer having a crosslinkable functional group. [8] The resin composition according to [6] or [7] above, which is for use as a sealant, adhesive, pressure sensitive adhesive or coating material.
[0012] [9] A method for producing a (meth)acrylic polymer, comprising: a step of producing a (meth)acrylic polymer (P1) having a thiocarbonylthio group by a reversible addition-fragmentation chain transfer living radical polymerization method; and a step of producing a (meth)acrylic polymer (P2) by reacting the thiocarbonylthio group of the (meth)acrylic polymer (P1) with a nucleophile, wherein the (meth)acrylic polymer (P2) has a glass transition temperature of -15°C or lower, at least one terminal structure in a molecular chain is a structure represented by the following formula (1), and has a Hazen color number (APHA) of 600 or less. [ka] (In formula (1), R represents a residue obtained by removing an acryloyloxy group from an acrylic ester compound contained in the monomer that constitutes the molecular chain.)
[10] The method for producing a (meth)acrylic polymer according to the above [9], wherein the (meth)acrylic polymer (P2) is a block copolymer having two or more polymer blocks. Effect of the Invention
[0013] According to the present invention, a (meth)acrylic polymer having little coloration and excellent weather resistance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. In this specification, "(meth)acrylic" means acrylic and / or methacrylic. "(meth)acrylate" means acrylate and / or methacrylate.
[0015] (Meth)acrylic polymer The (meth)acrylic polymer of the present invention (hereinafter also referred to as "the present polymer") is a polymer having a glass transition temperature of -15°C or lower, at least one terminal structure in the molecular chain being a structure represented by the following formula (1), and having a Hazen color unit number (APHA) of 600 or less. [ka] (In formula (1), R represents a residue obtained by removing an acryloyloxy group from an acrylic ester compound contained in a monomer that constitutes the molecular chain of the polymer.)
[0016] The glass transition temperature (Tg) of the polymer is -15°C or lower. If the Tg is higher than -15°C, the viscosity at room temperature (25°C) becomes too high, and it tends to be difficult to obtain a cured product with high weather resistance. In addition, when used as a base resin for applications such as sealing materials, adhesives, pressure sensitive adhesives, or paints, the handling properties are not good. From this viewpoint, the Tg of the polymer is preferably -20°C or lower, more preferably -25°C or lower, even more preferably -30°C or lower, even more preferably -35°C or lower, even more preferably -40°C or lower, even more preferably -45°C or lower, and particularly preferably -50°C or lower. The lower limit of the Tg of the polymer is not particularly limited, but is, for example, -80°C or higher, preferably -75°C or higher.
[0017] In this specification, the Tg of a polymer is a value measured by differential scanning calorimetry (DSC). Details of the measurement method follow the procedure described in the Examples below. The Tg of a polymer can be arbitrarily selected by changing the composition of the monomers constituting the polymer.
[0018] The APHA of the present polymer is 600 or less. If the APHA is higher than 600, the coloration is high, and the application to applications requiring low coloration is limited, which is not preferable. From the viewpoint of enabling application to applications requiring low coloration, the APHA of the present polymer is preferably 550 or less, more preferably 520 or less, even more preferably 500 or less, even more preferably 450 or less, even more preferably 400 or less, even more preferably 350 or less, and particularly preferably 300 or less. The lower limit of the APHA of the present polymer is not particularly limited, but from the viewpoint of ease of production, it is, for example, 30 or more.
[0019] In this specification, APHA is a value measured in accordance with JIS K 0071-1:2017, and the details are in accordance with the method described in the Examples below. The APHA of a polymer can be arbitrarily selected by changing the terminal structure, molecular weight, etc. of the polymer. For example, the APHA tends to decrease when the molecular weight of a polymer is increased.
[0020] At least one of the terminal structures of the molecular chain of the present polymer has a structure represented by the above formula (1). R in the above formula (1) represents a residue obtained by removing an acryloyloxy group from an acrylic acid ester compound contained in the monomer constituting the molecular chain of the present polymer, and specific examples thereof include an alkyl group, a cycloalkyl group, an alkylcycloalkyl group, an aryl group, and an aralkyl group having 1 to 30 carbon atoms. Examples of the acrylic acid ester compound constituting R in the above formula (1) include an acrylic acid alkyl ester compound, an aliphatic cyclic ester compound of (meth)acrylic acid, and an aromatic ester compound of acrylic acid. From the viewpoint of improving weather resistance, R is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 2 to 20 carbon atoms, and even more preferably an alkyl group having 4 to 18 carbon atoms.
[0021] Such present polymer can be obtained by a method including a step of polymerizing vinyl monomers including a (meth)acrylic monomer by reversible addition-fragmentation chain transfer living radical polymerization (RAFT) method to produce a (meth)acrylic polymer (P1) having a thiocarbonylthio group represented by the following formula (2) (hereinafter also referred to as a "polymerization step"), and a step of reacting the thiocarbonylthio group of the (meth)acrylic polymer (P1) with a nucleophile to produce the present polymer, that is, a (meth)acrylic polymer (P2) (hereinafter also referred to as a "reaction step"). [ka]
[0022] <Monomers that compose the molecular chain of this polymer> As the (meth)acrylic monomer constituting the molecular chain of the present polymer, at least one selected from the group consisting of (meth)acrylic acid alkyl ester compounds, (meth)acrylic acid aliphatic cyclic ester compounds, (meth)acrylic acid aromatic ester compounds, and compounds represented by the following formula (3) can be preferably used. CH 2 =CR 1 -C(=O)O-(R 2 O) n -R 3 …(3) (In formula (3), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms; R 3 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. n represents an integer of 1 to 100.
[0023] (Meth)acrylic acid alkyl ester compounds Specific examples of the (meth)acrylic acid alkyl ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and icosyl (meth)acrylate.
[0024] Of these, as the (meth)acrylic acid alkyl ester compound, a (meth)acrylic acid alkyl ester compound in which the alkyl group (R) in the alkyl ester portion (-COOR) has 1 to 20 carbon atoms can be preferably used, since it is easy to obtain a (meth)acrylic polymer having a low Tg and excellent fluidity. The (meth)acrylic acid alkyl ester compound constituting the present polymer is more preferably a (meth)acrylic acid alkyl ester compound having an alkyl group having 2 to 20 carbon atoms, further preferably includes a (meth)acrylic acid alkyl ester compound having an alkyl group having 2 to 18 carbon atoms, and even more preferably includes a (meth)acrylic acid alkyl ester compound having an alkyl group having 4 to 18 carbon atoms.
[0025] Aliphatic cyclic ester compounds of (meth)acrylic acid Specific examples of the aliphatic cyclic ester compounds of (meth)acrylic acid include cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.
[0026] Aromatic ester compounds of (meth)acrylic acid Specific examples of the aromatic ester compounds of (meth)acrylic acid include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxymethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, and 3-phenoxypropyl (meth)acrylate.
[0027] A compound represented by formula (3) Regarding the compound represented by the above formula (3), when n in the above formula (3) is 1, the compound represented by the above formula (3) has an oxyalkylene structure such as an oxyethylene chain, an oxypropylene chain, and an oxybutylene chain. Specific examples of the compound in which n in the above formula (3) is 1 (i.e., an (meth)acrylic acid alkoxyalkyl ester compound) include methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, n-propoxyethyl (meth)acrylate, n-butoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, n-propoxypropyl (meth)acrylate, n-butoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxybutyl (meth)acrylate, n-propoxybutyl (meth)acrylate, and n-butoxybutyl (meth)acrylate.
[0028] When n in the above formula (3) is 2 or more, the compound represented by the above formula (3) has a polyoxyalkylene structure such as a polyoxyethylene chain, a polyoxypropylene chain, or a polyoxybutylene chain. When n is 2 or more, two or more R 2 may be the same or different from each other. Therefore, the compound in which n in the above formula (3) is 2 or more may have different types of polyoxyalkylene structures in one molecule, such as a block structure consisting of polyoxyethylene / polyoxypropylene.
[0029] Specific examples of the compound in which n in the above formula (3) is 2 or more include polyoxyethylene (meth)acrylate, polyoxypropylene (meth)acrylate, polyoxybutylene (meth)acrylate, polyoxyethylene-polyoxypropylene (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, lauroxypolyethylene glycol (meth)acrylate, stearoxypolyethylene glycol (meth)acrylate, octoxypolyethylene glycol polypropylene glycol (meth)acrylate, nonylphenoxypolypropylene glycol (meth)acrylate, and phenoxypolyethylene glycol polypropylene glycol (meth)acrylate.
[0030] Among these, the (meth)acrylic monomer constituting the present polymer preferably contains a (meth)acrylic acid alkyl ester compound, from the viewpoint of high weather resistance and of easily obtaining a (meth)acrylic polymer having a low Tg and excellent fluidity, and more preferably contains a (meth)acrylic acid alkyl ester compound having an alkyl group having 2 to 18 carbon atoms. Moreover, the (meth)acrylic monomer constituting the present polymer more preferably contains an acrylic acid alkyl ester compound, from the viewpoint of at least containing an acrylic monomer and of being able to give a polymer having excellent weather resistance and fluidity.
[0031] In consideration of the mechanical properties of the present polymer, the present polymer preferably has a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 4 to 8 carbon atoms. In addition, in the case where another polymer (e.g., a polyoxyalkylene polymer) is blended into a resin composition containing the present polymer in preparing the resin composition, in consideration of increasing compatibility with the other polymer, the present polymer preferably has a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms, and more preferably has a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 10 to 18 carbon atoms.
[0032] In the present polymer, the content of structural units derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 4 to 8 carbon atoms is, from the viewpoint of obtaining a (meth)acrylic polymer that exhibits fluidity and has excellent mechanical properties, preferably 25 mass % or more, more preferably 30 mass % or more, even more preferably 40 mass % or more, and even more preferably 50 mass % or more, based on all structural units constituting the present polymer.
[0033] From the viewpoint of improving compatibility with other polymers, the content of structural units derived from an acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on all structural units constituting the present polymer. The upper limit is preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 5% by mass or less, based on all structural units constituting the present polymer.
[0034] In the present polymer, from the viewpoint of obtaining a (meth)acrylic polymer having sufficiently high fluidity, excellent mechanical properties, and excellent weather resistance, the content of structural units derived from (meth)acrylic acid alkyl ester compounds is preferably 40 mass% or more, more preferably 50 mass% or more, even more preferably 60 mass% or more, even more preferably 70 mass% or more, even more preferably 80 mass% or more, and even more preferably 90 mass% or more, based on all structural units constituting the present polymer.
[0035] In producing the present polymer, a vinyl monomer (hereinafter also referred to as "other monomer") other than the above-mentioned (meth)acrylic monomer and copolymerizable therewith may be used within the scope not impairing the effects of the present invention. Examples of the other monomer include styrene compounds, maleimide compounds, and amide group-containing vinyl compounds. The other monomer constituting the present polymer may be one or more of these.
[0036] Styrene-based compounds Specific examples of styrene-based compounds include styrene, α-methylstyrene, β-methylstyrene, vinylxylene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, pn-butylstyrene, p-isobutylstyrene, pt-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, p-hydroxystyrene, m-hydroxystyrene, o-hydroxystyrene, p-isopropenylphenol, m-isopropenylphenol, o-isopropenylphenol, o-vinylbenzoic acid, m-vinylbenzoic acid, p-vinylbenzoic acid, divinylbenzene, and vinylnaphthalene.
[0037] The amount of the styrene-based compound used is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total amount of monomers used in the polymerization reaction in this step.
[0038] Maleimide compounds Specific examples of the maleimide compound include maleimide and N-substituted maleimide compounds. Examples of the N-substituted maleimide compound include N-alkyl-substituted maleimide compounds such as N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, N-tert-butylmaleimide, N-pentylmaleimide, N-hexylmaleimide, N-heptylmaleimide, N-octylmaleimide, N-laurylmaleimide, and N-stearylmaleimide; N-cyclopentylmaleimide; imide, and N-cycloalkyl-substituted maleimide compounds such as N-cyclohexylmaleimide; and N-aryl-substituted maleimide compounds such as N-phenylmaleimide, N-(4-hydroxyphenyl)maleimide, N-(4-acetylphenyl)maleimide, N-(4-methoxyphenyl)maleimide, N-(4-ethoxyphenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, and N-benzylmaleimide.
[0039] The amount of the maleimide compound used is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total amount of monomers used in the polymerization reaction in this step.
[0040] Amide group-containing vinyl compounds Specific examples of the amide group-containing vinyl compound include (meth)acrylamide, (meth)acrylamide derivatives, and N-vinylamide monomers. Specific examples of the (meth)acrylamide derivatives include tert-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, and (meth)acryloylmorpholine. Specific examples of the N-vinylamide monomers include N-vinylacetamide, N-vinylformamide, and N-vinylisobutylamide.
[0041] The amount of the amide group-containing vinyl compound used is, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on the total amount of monomers used in the polymerization reaction in this step.
[0042] ·Crosslinkable functional group The present polymer preferably has a crosslinkable functional group in that the weather resistance and mechanical strength of the cured product obtained by using the present polymer can be improved. Examples of the crosslinkable functional group include a crosslinkable silyl group, a silanol group, a carboxyl group, a hydroxyl group, an epoxy group, an oxazoline group, an isocyanate group, and a polymerizable unsaturated group. Examples of the crosslinkable silyl group include an alkoxysilyl group and a halogenosilyl group. Among these, an alkoxysilyl group is preferred in that the reactivity is easily controlled, and examples of the alkoxysilyl group include a trimethoxysilyl group, a methyldimethoxysilyl group, a dimethylmethoxysilyl group, a triethoxysilyl group, a methyldiethoxysilyl group, and a dimethylethoxysilyl group.
[0043] When the present polymer has a crosslinkable functional group, the present polymer preferably has an average of 0.7 or more crosslinkable functional groups per molecule. The number of crosslinkable functional groups contained in one molecule of the present polymer is more preferably 1.0 or more, even more preferably 1.5 or more, and even more preferably 2.0 or more. The upper limit of the number of the crosslinkable functional groups is preferably 10 or less, more preferably 8.0 or less, and even more preferably 6.0 or less, in order to obtain a (meth)acrylic polymer having good elongation at break.
[0044] There is no particular limitation on the method of introducing a crosslinkable functional group into the present polymer, but the method of copolymerizing a vinyl monomer having a crosslinkable functional group is preferred because the crosslinkable functional group can be easily introduced into the polymer side chain. Examples of the vinyl monomer having a crosslinkable functional group include a crosslinkable silyl group-containing vinyl compound, an unsaturated carboxylic acid, an unsaturated acid anhydride, a hydroxyl group-containing vinyl compound, an epoxy group-containing vinyl compound, an oxazoline group-containing vinyl compound, and an isocyanate group-containing vinyl compound. The vinyl monomer having a crosslinkable functional group that constitutes the present polymer may be one of these, or two or more of them.
[0045] Examples of the crosslinkable silyl group-containing vinyl compound include vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, and vinyl dimethyl methoxysilane; alkoxysilyl group-containing (meth)acrylic acid esters such as trimethoxysilylpropyl (meth)acrylate, triethoxysilylpropyl (meth)acrylate, methyl dimethoxysilylpropyl (meth)acrylate, and dimethyl methoxysilylpropyl (meth)acrylate; alkoxysilyl group-containing vinyl ethers such as trimethoxysilylpropyl vinyl ether; and alkoxysilyl group-containing vinyl esters such as vinyl trimethoxysilyl undecanoate. The crosslinkable silyl group-containing vinyl compound forms a crosslinked structure by dehydration condensation between crosslinkable silyl groups, and is therefore suitable in that it can efficiently carry out the polymerization reaction when producing the present polymer and the subsequent crosslinking reaction.
[0046] In addition, the crosslinkable silyl group as a whole can be regarded as one reaction point. Therefore, in the present invention, the crosslinkable silyl group as a whole is regarded as one crosslinkable functional group. For example, vinyltrimethoxysilane is a compound having a trimethoxysilyl group as a crosslinkable functional group, and the number of crosslinkable functional groups in one molecule is one. In addition, vinylmethyldimethoxysilane is a compound having a methyldimethoxysilyl group as a crosslinkable functional group, and the number of crosslinkable functional groups in one molecule is one.
[0047] Examples of the unsaturated carboxylic acid include (meth)acrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, citraconic acid, cinnamic acid, and further, monoalkyl esters of unsaturated dicarboxylic acids (monoalkyl esters of maleic acid, fumaric acid, itaconic acid, citraconic acid, etc.), etc. Examples of the unsaturated acid anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, etc.
[0048] Examples of the hydroxy group-containing vinyl compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and mono(meth)acrylic acid esters of polyalkylene glycols (e.g., polyethylene glycol, polypropylene glycol, etc.). Examples of the epoxy group-containing vinyl compound include glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate. Among the compounds represented by the above formula (3), R 3 The compound in which is a hydrogen atom is also a vinyl monomer having a crosslinkable functional group.
[0049] Of these, the vinyl monomer having a crosslinkable functional group is preferably a crosslinkable silyl group-containing vinyl compound from the viewpoints of the breaking elongation and breaking strength of the cured product, as well as weather resistance.
[0050] Other methods for introducing a crosslinkable silyl group as a crosslinkable functional group include the following methods 1) and 2). 1) A method of introducing a crosslinkable silyl group into the side chain of a polymer by an addition reaction between a carboxyl group of an unsaturated carboxylic acid, which is a constituent monomer of the polymer, and an epoxy compound containing a crosslinkable silyl group. 2) A method of introducing a crosslinkable silyl group into the side chain of a polymer by an addition reaction between an epoxy group of an epoxy group-containing vinyl compound, which is a constituent monomer of the polymer, and an amine compound containing a crosslinkable silyl group.
[0051] In the above method 1), the unsaturated carboxylic acid is preferably at least one selected from the group consisting of (meth)acrylic acid, maleic anhydride, and itaconic acid. In the above method 2), the epoxy group-containing vinyl compound may be a glycidyl group-containing (meth)acrylic acid ester.
[0052] The method of introducing a polymerizable unsaturated group as a crosslinkable functional group includes a method of producing a polymer having a functional group in the molecule, and then reacting the polymer with a compound having a functional group and a polymerizable unsaturated group that can react with the functional group.Specific examples include a method of reacting a polymer having a hydroxyl group with a compound having both an isocyanate group and a polymerizable unsaturated group, and a method of reacting a polymer having a carboxyl group with a compound having both an epoxy group and a polymerizable unsaturated group.
[0053] In addition to the above, a crosslinkable functional group can also be introduced into the polymer by polymerization in the presence of a polymerization regulator such as a RAFT agent having a crosslinkable functional group.
[0054] In the present polymer, the content of the structural unit derived from a monomer having a crosslinkable functional group (hereinafter also referred to as "crosslinkable structural unit") is not particularly limited, but can be, for example, 0.01% by mass or more with respect to all structural units constituting the present polymer. If the content of the crosslinkable structural unit is 0.01% by mass or more, it is preferable in that the effect of improving the mechanical strength can be sufficiently obtained. The content of the crosslinkable structural unit in the present polymer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more. On the other hand, from the viewpoint of ensuring flexibility, the content of the crosslinkable structural unit is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and even more preferably 10% by mass or less with respect to all structural units constituting the present polymer.
[0055] <Block copolymer> A preferred embodiment of the present polymer is a block copolymer having two or more polymer blocks (hereinafter, also referred to as "block copolymer (P)"). The block copolymer (P) may have two or more polymer blocks having different monomer compositions, and its structure is not particularly limited. A preferred example of the block copolymer (P) is a (meth)acrylic polymer having a polymer block (A) having a crosslinkable functional group and a polymer block (B) having a monomer composition different from that of the polymer block (A).
[0056] Polymer block (A) Examples of the monomer constituting the polymer block (A) include the compounds exemplified as specific examples of the monomer constituting the present polymer. Of these, the polymer block (A) preferably has a structural unit derived from a (meth)acrylic acid alkyl ester compound, and more preferably has at least a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 2 to 18 carbon atoms.
[0057] In the polymer block (A), the content of the structural unit derived from the (meth)acrylic acid alkyl ester compound is preferably 50% by mass or more based on the total structural units constituting the polymer block (A) from the viewpoint of obtaining a polymer having excellent mechanical properties and excellent weather resistance. From this viewpoint, the content of the structural unit derived from the (meth)acrylic acid alkyl ester compound in the polymer block (A) is more preferably 55% by mass or more, even more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit of the content of the structural unit derived from the (meth)acrylic acid alkyl ester compound in the polymer block (A) is, for example, 99% by mass or less, preferably 98% by mass or less, and more preferably 95% by mass or less, from the viewpoint of fully obtaining the improvement effect due to the introduction of the crosslinkable functional group.
[0058] The content of the crosslinkable structural unit in the polymer block (A) is preferably 1% by mass or more based on all structural units constituting the polymer block (A). By setting the content of the crosslinkable structural unit to 1% by mass or more, it is preferable in that mechanical strength can be sufficiently improved. The content of the crosslinkable structural unit in the polymer block (A) is preferably 2% by mass or more, more preferably 5% by mass or more. On the other hand, from the viewpoint of ensuring the flexibility of the polymer, the upper limit of the crosslinkable structural unit is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less based on all structural units constituting the polymer block (A).
[0059] The number average molecular weight (Mn) of the polymer block (A) measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably in the range of 1,000 to 80,000. When Mn is 1,000 or more, it is preferable that the strength and durability of the cured product produced using the block copolymer (P) can be sufficiently increased. Also, when Mn is 80,000 or less, it is preferable that good flowability and coatability can be ensured.
[0060] From the viewpoint of strength of the cured product, the Mn of the polymer block (A) is more preferably 2,000 or more, more preferably 3,000 or more, even more preferably 4,000 or more, and even more preferably 5,000 or more. From the viewpoint of ensuring the flowability of the polymer, the upper limit of the Mn of the polymer block (A) is more preferably 60,000 or less, even more preferably 40,000 or less, even more preferably 20,000 or less, and even more preferably 10,000 or less. The preferred range of the Mn of the polymer block (A) can be set by appropriately combining the above-mentioned upper and lower limits. The Mn of the polymer block (A) is more preferably 2,000 to 60,000, even more preferably 3,000 to 40,000, even more preferably 4,000 to 20,000, and even more preferably 5,000 to 10,000.
[0061] When the block copolymer (P) has a plurality of polymer blocks (A), the number average molecular weight of the polymer block (A) represents the sum of the number average molecular weights of all the polymer blocks (A). For example, when the block copolymer (P) is an (A)-(B)-(A) triblock copolymer consisting of polymer block (A) / polymer block (B) / polymer block (A), the "number average molecular weight of the polymer block (A)" means the sum of the number average molecular weights of the two polymer blocks (A) contained in the block copolymer (P). The same applies to the polymer block (B).
[0062] The molecular weight distribution (Mw / Mn) of the polymer block (A), which is expressed by the ratio of the weight average molecular weight (Mw) and the number average molecular weight (Mn) in terms of polystyrene measured by GPC, is preferably 3.0 or less from the viewpoint of obtaining a polymer having excellent mechanical properties and weather resistance. The molecular weight distribution of the polymer block (A) is more preferably 2.5 or less, and further preferably 2.0 or less. The lower limit of the molecular weight distribution of the polymer block (A) is not particularly limited, but is, for example, 1.01 or more from the viewpoint of ease of production.
[0063] Polymer block (B) Examples of monomers constituting the polymer block (B) include the compounds exemplified as specific examples of monomers constituting the present polymer. Among the above monomers, the polymer block (B) is preferably a polymer having an acrylic acid alkyl ester compound as a main structural unit, more preferably a polymer having an acrylic acid alkyl ester compound having an alkyl group with 2 to 18 carbon atoms as a main structural unit, in that a (meth)acrylic monomer having excellent flexibility can be obtained, and particularly preferably a polymer having an acrylic acid alkyl ester compound having an alkyl group with 4 to 18 carbon atoms as a main structural unit.
[0064] In the polymer block (B), the content of structural units derived from an acrylic acid alkyl ester compound is preferably 50% by mass or more based on all structural units constituting the polymer block (B) from the viewpoint of obtaining a (meth)acrylic polymer having excellent mechanical properties. The content of structural units derived from an acrylic acid alkyl ester compound in the polymer block (B) is more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0065] In consideration of the fluidity of the block copolymer (P), the polymer block (B) preferably has a structural unit derived from an acrylic acid alkyl ester compound having an alkyl group having 4 to 8 carbon atoms. In addition, in consideration of improving compatibility with other polymers (e.g., polyoxyalkylene polymers) to be blended in a resin composition containing the block copolymer (P) when preparing the resin composition, the polymer block (B) preferably has a structural unit derived from an acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms, and more preferably has a structural unit derived from an acrylic acid alkyl ester compound having an alkyl group having 10 to 18 carbon atoms.
[0066] In the polymer block (B), the content of the structural units derived from an acrylic acid alkyl ester compound having an alkyl group having 4 to 8 carbon atoms is, from the viewpoint of obtaining a block copolymer (P) which exhibits sufficient fluidity and has excellent mechanical properties, preferably 40 mass % or more, more preferably 50 mass % or more, even more preferably 60 mass % or more, and even more preferably 70 mass % or more, based on the total structural units constituting the polymer block (B).
[0067] From the viewpoint of improving compatibility with other polymers, the content of structural units derived from an acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms (preferably 10 to 18 carbon atoms) is preferably 1% by mass or more, more preferably 5% by mass or more, based on all structural units constituting polymer block (B). The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, based on all structural units constituting polymer block (B).
[0068] The polymer block (B) may further have a crosslinkable functional group. When the polymer block (B) has a crosslinkable functional group, the crosslinkable functional group may be any of the groups exemplified as the crosslinkable functional group that the present polymer may have. From the viewpoint of forming a uniform crosslinked structure, it is preferable to concentrate crosslinking points in the polymer block (A). From this viewpoint, it is preferable that the ratio of the crosslinkable structural units to all structural units constituting the polymer block (B) is lower than the ratio of the crosslinkable structural units to all structural units constituting the polymer block (A).
[0069] Specifically, the content of the crosslinkable structural unit in the polymer block (B) is preferably 15% by mass or less based on all structural units constituting the polymer block (B). When the content of the crosslinkable structural unit in the polymer block (B) is 15% by mass or less, it is preferable in that the flexibility of the block copolymer (P) can be sufficiently ensured. In the polymer block (B), the content of the crosslinkable structural unit is preferably 10% by mass or less based on all structural units constituting the polymer block (B), more preferably 5% by mass or less, and even more preferably 2% by mass or less.
[0070] The number average molecular weight (Mn) of the polymer block (B) measured by GPC in terms of polystyrene is preferably in the range of 9,000 to 250,000. When Mn is 9,000 or more, it is preferable that the strength and durability of the cured product produced using the block copolymer (P) can be sufficiently increased. Also, when Mn is 250,000 or less, it is preferable that good fluidity and coatability can be ensured. Furthermore, when Mn of the polymer block (B) is in the above range, the molecular weight of the molecular chain portion corresponding to the distance between crosslinking points can be sufficiently ensured.
[0071] From the viewpoint of strength of the cured product, the Mn of the polymer block (B) is more preferably 14,000 or more, more preferably 19,000 or more, even more preferably 23,000 or more, and even more preferably 25,000 or more. From the viewpoint of ensuring the flowability of the polymer, the upper limit of the Mn of the polymer block (B) is more preferably 150,000 or less, even more preferably 100,000 or less, even more preferably 80,000 or less, and even more preferably 55,000 or less. The preferred range of the Mn of the polymer block (B) can be set by appropriately combining the above-mentioned upper and lower limits. The Mn of the polymer block (B) is more preferably 14,000 to 150,000, even more preferably 19,000 to 100,000, even more preferably 23,000 to 80,000, and even more preferably 25,000 to 55,000.
[0072] The molecular weight distribution (Mw / Mn) of the polymer block (B), which is expressed by the ratio of Mw and Mn in terms of polystyrene measured by GPC, is preferably 3.0 or less from the viewpoint of obtaining a polymer having excellent weather resistance. The molecular weight distribution of the polymer block (B) is more preferably 2.5 or less, further preferably 2.2 or less, and further preferably 2.0 or less. The lower limit of the molecular weight distribution of the polymer block (B) is not particularly limited, but is, for example, 1.01 or more from the viewpoint of ease of production.
[0073] Block copolymer (P) composition Specific examples of the block copolymer (P) having a polymer block (A) and a polymer block (B) include an (A)-(B) diblock consisting of a polymer block (A) and a polymer block (B), an (A)-(B)-(A) triblock consisting of a polymer block (A) / polymer block (B) / polymer block (A), a (B)-(A)-(B) triblock consisting of a polymer block (B) / polymer block (A) / polymer block (B), and an (A)-(B)-(A)-(B)-(A) pentablock consisting of a polymer block (A) / polymer block (B) / polymer block (A) / polymer block (B) / polymer block (A). The block copolymer (P) may further have a polymer block (C) other than the polymer block (A) and the polymer block (B). Examples of the monomer constituting the polymer block (C) include the compounds exemplified as specific examples of the monomer constituting the present polymer.
[0074] Of these, the block copolymer (P) is preferably a triblock copolymer, and more preferably an (A)-(B)-(A) triblock copolymer, in that the number of blocks is as small as possible to ensure ease of production while providing a polymer that exhibits excellent weather resistance. With such a structure, the polymer block (A) having a crosslinkable structural unit acts as a crosslinking segment, so that a uniform crosslinked structure is easily formed while ensuring the molecular weight between crosslinking points, and the mechanical strength and weather resistance of the resulting cured product can be increased, which is preferable.
[0075] In the block copolymer (P), the ratio of the polymer block (A) and the polymer block (B) is not particularly limited, but from the viewpoint of sufficiently introducing crosslinking points into the block copolymer (P) to obtain a polymer having high mechanical strength and weather resistance, the content of the polymer block (A) is preferably 2 parts by mass or more per 100 parts by mass of the total amount of the polymer block (A) and the polymer block (B). The content of the polymer block (A) is more preferably 4 parts by mass or more, more preferably 6 parts by mass or more, even more preferably 8 parts by mass or more, and even more preferably 10 parts by mass or more per 100 parts by mass of the total amount of the polymer block (A) and the polymer block (B). The upper limit of the content of the polymer block (A) is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less per 100 parts by mass of the total amount of the polymer block (A) and the polymer block (B).
[0076] The number average molecular weight (Mn) of the block copolymer (P) measured by GPC in terms of polystyrene is preferably in the range of 10,000 to 300,000. When Mn is 10,000 or more, it is preferable that the strength and weather resistance of the cured product produced using the block copolymer (P) can be sufficiently increased. On the other hand, when Mn is 300,000 or less, it is preferable that good fluidity and coatability can be ensured.
[0077] From the viewpoint of strength and weather resistance of the cured product, Mn of the block copolymer (P) is more preferably 15,000 or more, even more preferably 20,000 or more, even more preferably 25,000 or more, and even more preferably 30,000 or more. From the viewpoint of ensuring the flowability of the polymer, the upper limit of Mn of the block copolymer (P) is more preferably 200,000 or less, even more preferably 150,000 or less, even more preferably 90,000 or less, and even more preferably 70,000 or less. The preferred range of Mn of the block copolymer (P) is more preferably 15,000 to 200,000, even more preferably 20,000 to 150,000, even more preferably 25,000 to 90,000, and even more preferably 30,000 to 70,000.
[0078] The viscosity of the block copolymer (P) is 0.5×10 4 ~1.0×10 6 When the viscosity is within this range, a polymer having good fluidity and coatability and high mechanical strength can be obtained. From the viewpoint of obtaining a polymer having sufficiently high mechanical strength, the viscosity of the block copolymer (P) is preferably 1.0×10 4 More preferably, 1.5×10 4 The upper limit of the viscosity is preferably 9.0×10 to ensure flowability and coatability. 5 Less than or equal to 8.0×10 is preferable. 5 The following is more preferred. The viscosity of the block copolymer (P) is an E-type viscosity measured at 25° C. Details of the viscosity measurement method are as described in the following Examples.
[0079] <Production of Block Copolymer (P)> As described above, the block copolymer (P) can be obtained by producing a (meth)acrylic polymer (P1) having a thiocarbonylthio group in a polymerization step by the RAFT method, and then reacting the thiocarbonylthio group of the (meth)acrylic polymer (P1) with a nucleophilic agent in a reaction step. The above-mentioned (meth)acrylic polymer (P2) corresponds to the block copolymer (P).
[0080] (Polymerization process) The (meth)acrylic polymer (P1) can be obtained by polymerizing vinyl monomers by the RAFT method. For example, in the case of a solution polymerization method, an organic solvent and monomers are charged into a reactor, a polymerization initiator is added, and the resulting copolymer is preferably heated to obtain the desired (meth)acrylic polymer (P1). The method of charging each raw material may be a batch-type initial lump-sum charge in which all raw materials are charged at once, a semi-continuous charge in which at least a part of the raw materials is continuously fed into the reactor, or a continuous polymerization method in which all raw materials are continuously fed and the product is continuously withdrawn from the reactor at the same time.
[0081] In the RAFT method, polymerization proceeds through a reversible chain transfer reaction in the presence of a polymerization control agent (RAFT agent) and a radical polymerization initiator. As the RAFT agent, a compound having a thiocarbonylthio group (a group represented by the above formula (2)), such as a dithioester compound, a xanthate compound, a trithiocarbonate compound, and a dithiocarbamate compound, can be used. It is preferable to use a RAFT agent containing a trithiocarbonate group. As a compound having a trithiocarbonate group, for example, S,S-dibenzyl trithiocarbonate, bis[4-(2,3-dihydroxypropoxycarbonyl)benzyl]trithiocarbonate, bis[4-(2-hydroxyethoxycarbonyl)benzyl]trithiocarbonate, and 1,4-bis(alkylsulfanylthiocarbonylsulfanylmethyl)benzene (for example, 1,4-bis(n-dodecylsulfanylthiocarbonylsulfanylmethyl)benzene, etc.) can be mentioned. In the polymerization reaction, the amount of the RAFT agent used is appropriately adjusted depending on the types of monomer and RAFT agent used, etc.
[0082] As the radical polymerization initiator used in the polymerization by the RAFT method, known radical polymerization initiators such as azo compounds, organic peroxides and persulfates can be used. Among these, azo compounds are preferred because they are safe and easy to handle, and side reactions during radical polymerization are unlikely to occur. Specific examples of azo compounds include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), and the like. The radical polymerization initiator may be used alone or in combination of two or more kinds.
[0083] The amount of radical polymerization initiator used is not particularly limited, but from the viewpoint of obtaining a polymer with a narrower molecular weight distribution, it is preferably 0.5 mol or less, more preferably 0.4 mol or less, per 1 mol of the RAFT agent. Also, from the viewpoint of stably carrying out the polymerization reaction, the lower limit of the amount of radical polymerization initiator used is preferably 0.01 mol or more, more preferably 0.05 mol or more, per 1 mol of the RAFT agent. The amount of radical polymerization initiator used per 1 mol of the RAFT agent is preferably 0.01 to 0.5 mol, more preferably 0.05 to 0.4 mol.
[0084] The polymerization reaction is preferably carried out in a solvent using a polymerization solvent known in living radical polymerization. The polymerization solvent used is preferably an organic solvent capable of dissolving the monomer, and examples thereof include aromatic compounds such as benzene, toluene, xylene, and anisole; ester compounds such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone compounds such as acetone, methyl ethyl ketone, and cyclohexanone; dimethylformamide, acetonitrile, dimethyl sulfoxide, and alcohol. Water may also be used as the polymerization solvent. The polymerization solvent may be used alone or in combination of two or more. The (meth)acrylic polymer (P1) may also be produced by bulk polymerization or the like without using a polymerization solvent.
[0085] When the polymerization reaction is carried out in a solvent, the amount of the polymerization solvent used is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, relative to 100 parts by mass of the total amount of the monomers used in the reaction. When the amount of the polymerization solvent used is 100 parts by mass or less, it is preferable in that a high reaction rate can be achieved in a short time.
[0086] In the polymerization reaction by the RAFT method, the reaction temperature is preferably 40° C. or more and 100° C. or less, more preferably 45° C. or more and 90° C. or less, and even more preferably 50° C. or more and 80° C. or less. A reaction temperature of 40° C. or more is preferable in that the polymerization reaction can proceed smoothly, and a reaction temperature of 100° C. or less is preferable in that side reactions can be suppressed and restrictions on initiators and solvents that can be used are relaxed. The reaction time can be appropriately set depending on the monomers used, etc., but is preferably 1 hour or more and 48 hours or less, and more preferably 2 hours or more and 24 hours or less.
[0087] The polymerization reaction may be carried out in the presence of a chain transfer agent such as an alkylthiol compound having 2 to 20 carbon atoms, if necessary. When a polymer solution is obtained by the above polymerization, the polymer can be isolated by subjecting the polymer solution to a known solvent removal treatment. Alternatively, the obtained polymer solution may be used as is to carry out the next reaction step. In addition, a dehydrating agent such as trimethyl orthoacetate or triethyl orthoacetate may be mixed into the reaction system, if necessary. By adding a dehydrating agent to the reaction system, it is possible to suppress the progress of the crosslinking reaction during polymerization.
[0088] For example, when a (A)-(B)-(A)-(B)-(A) pentablock consisting of polymer block (A) / polymer block (B) / polymer block (A) / polymer block (B) / polymer block (A) is obtained by a RAFT method using S,S-dibenzyl trithiocarbonate as a RAFT agent, it is preferable in that the target product can be obtained efficiently by a method including the following three polymerization steps. That is, in the first polymerization step, a polymer block (A) is obtained using a monomer constituting the polymer block (A), and then, in the second polymerization step, a monomer constituting the polymer block (B) is polymerized to obtain a polymer block (B). This makes it possible to obtain an (A)-(B)-(A) triblock consisting of polymer block (A) / polymer block (B) / polymer block (A). Furthermore, in the third polymerization step, a monomer constituting the polymer block (A) is polymerized to obtain a polymer block (A). This makes it possible to obtain, as the (meth)acrylic polymer (P1), an (A)-(B)-(A)-(B)-(A) pentablock copolymer consisting of polymer block (A)-polymer block (B)-polymer block (A)-polymer block (B)-polymer block (A). Moreover, by using a similar method, it is possible to obtain, as the (meth)acrylic polymer (P1), a block copolymer having a higher order than the pentablock copolymer.
[0089] (Reaction process) Next, the thiocarbonylthio group of the (meth)acrylic polymer (P1) obtained by the polymerization step is reacted with a nucleophile. Through this reaction, a thiol group is generated from the thiocarbonylthio group of the (meth)acrylic polymer (P1), and the generated thiol group is reacted with an acrylic acid ester compound contained in the monomer constituting the (meth)acrylic polymer (P1), thereby obtaining a (meth)acrylic polymer having a terminal structure represented by the above formula (1).
[0090] The method of making the acrylic acid ester compound contained in the monomer constituting the (meth)acrylic polymer (P1) present in the reaction system when the thiocarbonylthio group of the (meth)acrylic polymer (P1) reacts with the nucleophile includes the following: [1] A method of making the monomer reaction rate less than 100% in the polymerization step, and making the remaining monomer (more specifically, the remaining acrylate monomer) present after the polymerization of the (meth)acrylic polymer (P1) is completed; [2] A method of adding the acrylic acid ester compound contained in the monomer constituting the (meth)acrylic polymer (P1) when the thiocarbonylthio group of the (meth)acrylic polymer (P1) reacts with the nucleophile; and a combination of these. Among these, the method [1] does not require the step of adding the acrylic acid ester compound, and can simplify the process.
[0091] For example, when S,S-dibenzyl trithiocarbonate is used as the RAFT agent in the polymerization step to obtain a triblock copolymer as the (meth)acrylic polymer (P1), the block copolymer (P) can be obtained as a diblock copolymer. When S,S-dibenzyl trithiocarbonate is used as the RAFT agent in the polymerization step to obtain a pentablock copolymer as the (meth)acrylic polymer (P1), the block copolymer (P) can be obtained as a triblock copolymer. When S,S-dibenzyl trithiocarbonate is used as the RAFT agent, one end structure in the molecular chain of the obtained block copolymer (P) becomes the structure represented by the above formula (1).
[0092] In addition, when 1,4-bis(alkylsulfanylthiocarbonylsulfanylmethyl)benzene is used as a RAFT agent in the polymerization step to obtain a tetrablock copolymer as the (meth)acrylic polymer (P1), the block copolymer (P) can be obtained as a tetrablock copolymer. In this case, the block copolymer (P) can be a (meth)acrylic polymer having the structure represented by the above formula (1) at both ends of the molecular chain.
[0093] Examples of the nucleophilic agent include ammonia, primary and / or secondary amine compounds, alkali metal alkoxides, hydroxides, and thiols. Among these, from the viewpoint of reactivity, primary and / or secondary amine compounds can be preferably used as the nucleophilic agent. It is presumed that the thiocarbonylthio group of the (meth)acrylic polymer (P1) is reacted with the nucleophilic agent to convert the thiocarbonylthio group into a thiol group, and the thiol group reacts with the acrylate compound in the reaction system (Michael addition reaction), thereby obtaining a (meth)acrylic polymer having a terminal structure represented by the above formula (1).
[0094] The molar equivalent of the nucleophile relative to the thiocarbonylthio group is preferably 2 to 90 molar equivalents. From the viewpoint of reaction efficiency, the amount of the nucleophile used is preferably 2.5 molar equivalents or more relative to the thiocarbonylthio group, more preferably 3 molar equivalents or more, and even more preferably 3.5 molar equivalents or more. In addition, from the viewpoint of reducing the influence of odor due to unreacted nucleophile, the amount of the nucleophile used is preferably 75 molar equivalents or less relative to the thiocarbonylthio group, more preferably 60 molar equivalents or less, and even more preferably 50 molar equivalents or less. The molecular weight of the nucleophile is preferably 150 or less, more preferably 110 or less, and even more preferably 60 or less, from the viewpoint of easy removal of unreacted nucleophile.
[0095] The reactor used in the reaction of the thiocarbonylthio group with the nucleophile may be a known reactor such as a batch reactor or a tubular reactor. Of these, a batch reactor is preferred because there is less risk of clogging, which is a problem in tubular reactors. The reaction temperature is preferably 10°C or higher, more preferably 15°C or higher, and even more preferably 25°C or higher, from the viewpoint of reaction efficiency. In addition, in order to prevent side reactions (e.g., nucleophilic reactions to the polymer main chain, etc.), the reaction temperature is preferably 80°C or lower, more preferably 60°C or lower, and even more preferably 50°C or lower. The reaction pressure may usually be normal pressure, but may be increased or reduced as necessary. The reaction time is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 3 hours or more, from the viewpoint of reaction efficiency. In addition, in order to suppress side reactions such as nucleophilic reactions to the polymer main chain, it is preferably 48 hours or less, more preferably 36 hours or less, and even more preferably 24 hours or less. When a polymer solution is obtained by the above reaction, the polymer can be isolated by subjecting this polymer solution to a known solvent removal treatment.
[0096] 《Resin composition》 The polymer has high weather resistance and is therefore suitable for use in sealants, adhesives, pressure sensitive adhesives, paints, etc. In addition, the polymer has low APHA and can be used in applications requiring low colorability. The polymer can be used alone in applications such as sealants, adhesives, pressure sensitive adhesives, paints, etc., but may also be used as a resin composition containing various components such as known additives, if necessary.
[0097] When the present block copolymer has a crosslinkable functional group, the present composition can be made into a curable resin composition by blending a necessary crosslinking agent, other polymers having a crosslinkable functional group, a crosslinking accelerator, etc. according to the type of the crosslinkable functional group. By molding such a curable resin composition and subjecting it to a heat treatment or the like as necessary, a cured product according to the application can be obtained.
[0098] · Crosslinking agent (hardening agent) Examples of the crosslinking agent (curing agent) include an epoxy compound having two or more epoxy groups, an isocyanate compound having two or more isocyanate groups, an aziridine compound having two or more aziridinyl groups, an oxazoline compound having an oxazoline group, a metal chelate compound, a butylated melamine compound, etc. Among these, the crosslinking agent is preferably an epoxy compound, an isocyanate compound, or an aziridine compound, and among these, an isocyanate compound is preferred in that a cured product having good physical properties under high temperature conditions can be obtained.
[0099] Examples of the epoxy compound include polyfunctional glycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerin diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidylxylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and sorbitol polyglycidyl ether.
[0100] Examples of the isocyanate compound include various aromatic, aliphatic and alicyclic isocyanate compounds, as well as modified products of these isocyanate compounds (modified isocyanates). Examples of the aromatic isocyanate include diphenylmethane diisocyanate (MDI), crude diphenylmethane diisocyanate, tolylene diisocyanate, naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), xylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), tolidine diisocyanate (TODI), and the like. Examples of the aliphatic isocyanate include hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI), and lysine triisocyanate (LTI). Examples of the alicyclic isocyanate include isophorone diisocyanate (IPDI), cyclohexyl diisocyanate (CHDI), hydrogenated XDI (H6XDI), and hydrogenated MDI (H12MDI). Examples of modified isocyanates include urethane-modified, dimer-, trimer-, carbodiimide-, allophanate-, biuret-, urea-, isocyanurate-, oxazolidone-, and isocyanate-terminated prepolymers of the above-mentioned isocyanate compounds.
[0101] Examples of the aziridine compound include 1,6-bis(1-aziridinylcarbonylamino)hexane, 1,1'-(methylene-di-p-phenylene)bis-3,3-aziridyl urea, 1,1'-(hexamethylene)bis-3,3-aziridyl urea, ethylene bis-(2-aziridinyl propionate), tris(1-aziridinyl)phosphine oxide, 2,4,6-triaziridinyl-1,3,5-triazine, and trimethylolpropane-tris-(2-aziridinyl propionate).
[0102] When the resin composition contains a crosslinking agent, the content is usually 0.01 to 10 parts by mass relative to 100 parts by mass of the present polymer, preferably 0.03 to 5 parts by mass, more preferably 0.05 to 2 parts by mass.
[0103] Other polymers with crosslinkable functional groups Examples of other polymers having a crosslinkable functional group include polyoxyalkylene polymers having a crosslinkable functional group, (meth)acrylic polymers having a crosslinkable functional group and different from the present polymer, polyester polymers having a crosslinkable functional group, polyurethane polymers having a crosslinkable functional group, polybutadiene polymers having a crosslinkable functional group, hydrogenated polybutadiene polymers having a crosslinkable functional group, and hydrocarbon polymers such as polyisobutylene polymers having a crosslinkable functional group; polyamide polymers; bisphenol polymers, etc. Among these, the resin composition of the present invention preferably contains a polyoxyalkylene polymer having a crosslinkable functional group together with the present polymer, in terms of excellent mechanical properties of the cured product. Examples of the crosslinkable functional group possessed by the other polymer include the groups exemplified as the crosslinkable functional group that the present polymer may have.
[0104] The polyoxyalkylene polymer having a crosslinkable functional group (hereinafter also referred to as "polyoxyalkylene polymer (Q)") may be a polymer having a repeating unit represented by the following formula (5). -OR 1 - …(5) (In formula (5), R 1 represents a divalent hydrocarbon group.
[0105] R in the above formula (5) 1 Examples of such structures include the following. -(CH 2 ) n - (n is an integer between 1 and 10) -CH(CH 3 )CH 2 - -CH(C 2 H 5 )CH 2 - -C(CH 3 ) 2 CH 2 - The polyoxyalkylene polymer (Q) may contain one or a combination of two or more of the repeating units described above. Among these, the -CH(CH 3 )CH2 - is preferred.
[0106] As the crosslinkable functional group of the polyoxyalkylene polymer (Q), a crosslinkable silyl group is preferred from the viewpoints of excellent compatibility with the present polymer, excellent mechanical properties of the cured product, and excellent weather resistance, and an alkoxysilyl group is more preferred from the viewpoint of easy control of reactivity.
[0107] The method for producing the polyoxyalkylene polymer (Q) is not particularly limited, and examples thereof include a polymerization method using a corresponding epoxy compound or diol compound as a raw material, with an alkali catalyst (e.g., KOH, etc.), a polymerization method using a transition metal compound-porphyrin complex catalyst, a polymerization method using a composite metal cyanide complex catalyst, and a polymerization method using phosphazene.
[0108] The average number of crosslinkable silyl groups contained in one molecule of the polyoxyalkylene polymer (Q) is preferably in the range of 1 to 4, more preferably in the range of 1.5 to 3, from the viewpoint of the mechanical properties and adhesiveness of the cured product. The position of the crosslinkable silyl group contained in the polyoxyalkylene polymer (Q) is not particularly limited, and it can be in the side chain and / or at the end of the polymer. The polyoxyalkylene polymer (Q) to be blended in the resin composition may be either a linear polymer or a branched polymer. These may also be used in combination.
[0109] The polystyrene-equivalent number average molecular weight (Mn) of the polyoxyalkylene polymer (Q) measured by GPC is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more, from the viewpoint of mechanical properties. The upper limit of Mn is preferably 60,000 or less, more preferably 50,000 or less, and even more preferably 40,000 or less, from the viewpoint of improving the workability (viscosity) when applying the curable resin composition. The range of Mn can be set by combining the above upper and lower limits, and is preferably 5,000 or more and 60,000 or less, more preferably 10,000 or more and 60,000 or less, and even more preferably 15,000 or more and 50,000 or less.
[0110] Commercially available products may be used as the polyoxyalkylene polymer (Q). Specific examples include "MS Polymer S203", "MS Polymer S303", "MS Polymer S810", "Silyl SAT200", "Silyl SAT350", "Silyl EST280" and "Silyl SAT30" manufactured by Kaneka Corporation, and "Exestar ES-S2410", "Exestar ES-S2420" and "Exestar ES-S3430" (all trade names) manufactured by AGC Inc.
[0111] When the resin composition contains a polyoxyalkylene polymer (Q), the content is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the total amount of the present polymer and the polyoxyalkylene polymer (Q). By setting the content of the polyoxyalkylene polymer (Q) within the above range, it is preferable in that a cured product having high mechanical properties can be obtained. In addition, the upper limit of the content of the polyoxyalkylene polymer (Q) is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less, based on 100 parts by mass of the total amount of the present polymer and the polyoxyalkylene polymer (Q), from the viewpoint of obtaining a cured product exhibiting excellent weather resistance.
[0112] Examples of other components added to the resin composition include, in addition to those mentioned above, plasticizers, fillers, adhesion promoters, dehydrating agents, curing accelerators, antioxidants, ultraviolet absorbers, and oils.
[0113] Examples of the plasticizer include liquid polyurethane resin, polyester-based plasticizers obtained from dicarboxylic acid and diol; etherified or esterified polyalkylene glycols such as polyethylene glycol and polypropylene glycol; polyether-based plasticizers such as saccharide-based polyethers obtained by addition polymerization of alkylene oxides such as ethylene oxide and propylene oxide to saccharide polyhydric alcohols such as sucrose, followed by etherification or esterification; polystyrene-based plasticizers such as poly-α-methylstyrene; and poly(meth)acrylates having no crosslinkable functional groups. Among these, poly(meth)acrylates having no crosslinkable functional groups are preferred in terms of durability such as weather resistance of the cured product. As the plasticizer, a polymer having Mw in the range of 1,000 to 7,000 and a glass transition temperature of -30°C or less is preferred.
[0114] The amount of the plasticizer used is preferably in the range of 0 to 100 parts by mass, may be in the range of 0 to 80 parts by mass, or may be in the range of 0 to 50 parts by mass, relative to 100 parts by mass of the total amount of the polyoxyalkylene polymer (Q) and the present block copolymer.
[0115] Examples of the filler include light calcium carbonate having an average particle size of about 0.02 to 2.0 μm, heavy calcium carbonate having an average particle size of about 1.0 to 5.0 μm, titanium oxide, carbon black, synthetic silicic acid, talc, zeolite, mica, silica, calcined clay, kaolin, bentonite, aluminum hydroxide, barium sulfate, glass balloons, silica balloons, and polymethyl methacrylate balloons. These fillers improve the mechanical properties of the cured product, and can increase the tensile strength and tensile elongation.
[0116] Among these, the filler is preferably light calcium carbonate, heavy calcium carbonate, or titanium oxide, and more preferably a mixture of light calcium carbonate and heavy calcium carbonate, in terms of the high effect of improving physical properties. The amount of the filler is preferably 20 to 300 parts by mass, more preferably 50 to 200 parts by mass, based on 100 parts by mass of the total amount of the polyoxyalkylene polymer (Q) and the present polymer. When a mixture of light calcium carbonate and heavy calcium carbonate is used, the ratio of light calcium carbonate / heavy calcium carbonate is preferably in the range of 90 / 10 to 50 / 50 by mass.
[0117] Examples of adhesion promoters include aminosilanes such as those sold under the trade names "KBM602", "KBM603", "KBE602", "KBE603", "KBM902" and "KBM903" by Shin-Etsu Silicones Co., Ltd. Examples of dehydrating agents include methyl orthoformate, methyl orthoacetate and vinylsilane.
[0118] As the curing accelerator, known compounds such as tin-based catalysts, titanium-based catalysts, and tertiary amines can be used. Among these, examples of tin-based catalysts include dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetonate, and dioctyltin dilaurate. Specific examples include products manufactured by Nitto Kasei Co., Ltd. under the trade names "Neostan U-28", "Neostan U-100", "Neostan U-200", "Neostan U-220H", "Neostan U-303", and "SCAT-24". Examples of titanium catalysts include tetraisopropyl titanate, tetra-n-butyl titanate, titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethyl acetylacetonate, dibutoxytitanium diacetylacetonate, diisopropoxytitanium diacetylacetonate, titanium octylene glycolate, and titanium lactate. Examples of tertiary amines include triethylamine, tributylamine, triethylenediamine, hexamethylenetetramine, 1,8-diazabicyclo[5,4,0]undecene-7 (DBU), diazabicyclononene (DBN), N-methylmorpholine, and N-ethylmorpholine.
[0119] The amount of the curing accelerator to be added is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the total amount of the polyoxyalkylene polymer (Q) and the present polymer.
[0120] As the antiaging agent, ultraviolet absorbers such as benzophenone compounds, benzotriazole compounds, and anilide oxalate compounds, light stabilizers such as hindered amine compounds, antioxidants such as hindered phenols, heat stabilizers, and mixtures thereof can be used.
[0121] Examples of ultraviolet absorbents include BASF's trade names "Tinuvin 571", "Tinuvin 1130" and "Tinuvin 327". Examples of light stabilizers include BASF's trade names "Tinuvin 292", "Tinuvin 144" and "Tinuvin 123", and Sankyo's trade name "Sanol 770". Examples of heat stabilizers include BASF's trade names "Irganox 1135", "Irganox 1520" and "Irganox 1330". In addition, BASF's trade name "Tinuvin B75", which is a mixture of ultraviolet absorbent / light stabilizer / heat stabilizer, may be used.
[0122] For the purpose of adjusting the performance, coatability, processability, etc. of the resin composition containing the present polymer, other thermoplastic resins, etc. may be blended into the resin composition. Specific examples of thermoplastic resins include polyolefin resins such as polyethylene and polypropylene, styrene resins such as polystyrene, vinyl resins such as polyvinyl chloride, polyester resins, polyamide resins, etc. Also, a known elastomer may be blended.
[0123] The resin composition of the present invention can be prepared as a one-component curable resin composition in which all ingredients are mixed in advance and stored in a sealed state, and the composition is cured by absorbing moisture in the air after application. It can also be prepared as a two-component curable resin composition in which ingredients such as a curing catalyst, a filler, a plasticizer, and water are mixed separately as a curing agent, and the curing agent and the resin composition are mixed before use. Of these, the one-component type is more preferred in terms of ease of handling and the ability to prevent mixing errors during application.
[0124] The resin composition containing the present polymer exhibits good fluidity when heated to room temperature (25° C.) to about 150° C. Therefore, it can be applied to various coating processes as well as molding processes using various methods such as extrusion molding, injection molding, and casting. EXAMPLES
[0125] The present disclosure will be specifically described below based on examples, but the present disclosure is not limited to these examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified. The details of the analysis method of the polymers obtained in the synthesis examples, comparative synthesis examples, production examples, and comparative production examples, and the preparation and evaluation methods of the resin compositions are as follows.
[0126] <Polymer analysis method> <Molecular weight measurement> The resulting polymer was subjected to gel permeation chromatography (GPC) under the conditions described below to obtain the number average molecular weight (Mn) and weight average molecular weight (Mw) in terms of polystyrene. The molecular weight distribution (Mw / Mn) was calculated from the obtained values. Measurement conditions Column: Tosoh TSKgel SuperMultiporeHZ-M x 4 Solvent: Tetrahydrofuran Temperature: 40℃ Detector: RI Flow rate: 600μL / min
[0127] <Viscosity measurement> The E-type viscosity was measured under the following conditions using a TVE-20H viscometer (cone / plate type, manufactured by Toki Sangyo Co., Ltd.). Measurement conditions Cone shape: angle 3°, radius 7.7mm Temperature: 25℃±0.5℃ Measurable range: 7,500 to 1,500,000 mmPa·s
[0128] <Measurement of glass transition temperature (Tg)> The glass transition temperature (Tg) of the polymer was determined from the intersection of the tangent at the inflection point and the baseline of the heat flux curve obtained using a differential scanning calorimeter. The heat flux curve was obtained by heating about 10 mg of a sample from 30°C to 100°C at 10°C / min, holding it for 1 minute, subsequently cooling it to -100°C, holding it for 5 minutes, and then heating it up to 100°C at 10°C / min. Measuring equipment: SII NanoTechnology DSC6220 Measurement atmosphere: Nitrogen atmosphere <Measurement of monomer reaction rate> The reaction rate [%] of the monomer was determined by gas chromatography (GC) measurement.
[0129] <Measurement of Hazen unit color number (APHA)> In accordance with the Hazen unit color number test using an ultraviolet-visible spectrophotometer as specified in JIS K 0071-1:2017, several Hazen unit color number standard solutions were measured using a color difference meter (manufactured by Nippon Denshoku Industries Co., Ltd., petroleum product color tester, product name "OME-2000") to obtain the tristimulus value (X, Y, Z) from which the yellowness index (YI) was calculated. The Hazen unit color number (APHA) of the standard solution and the calibration curve of YI (APHA = 0.1486 * YI 2 -9.7627*YI+495.11) was prepared. Separately, the YI of each polymer was measured using the color difference meter, and the APHA of each polymer was calculated using the calibration curve.
[0130] <Preparation of resin composition> In the examples and comparative examples, the components were mixed according to the mixing ratios shown in Table 1 (mixtures A and B), and resin compositions were prepared according to a conventional method. In Table 1, the (meth)acrylic polymers used were the polymers obtained in the following production examples and comparative production examples.
[0131] [Table 1]
[0132] The abbreviations in Table 1 have the following meanings. Polyoxyalkylene polymer X: A polypropylene glycol obtained in the synthesis example described below with its both ends silylated. UP-1110: Acrylic plasticizer, ARUFON (registered trademark) UP-1110 (manufactured by Toagosei Co., Ltd.) ·DIDP: Plasticizer, diisodecyl phthalate Light calcium carbonate: filler, Hakuenka CCR (manufactured by Shiraishi Calcium Co., Ltd.) Heavy calcium carbonate: Filler, Super SS (manufactured by Maruo Calcium Co., Ltd.) R820: Pigment, titanium oxide R-820 (manufactured by Ishihara Sangyo Kaisha) B75: Anti-aging agent, Tinuvin B75 (manufactured by BASF Japan) SH6020: Adhesion promoter, 3-(2-aminoethyl)aminopropyltrimethoxysilane, SH6020 (manufactured by Dow Corning Toray Co., Ltd.) SZ6300: Dehydrating agent, vinyltrimethoxysilane, SZ6300 (manufactured by Dow Corning Toray Co., Ltd.) U-220H: Curing catalyst, dibutyltin diacetylacetonate, Neostan U-220H (manufactured by Nitto Kasei Co., Ltd.)
[0133] <Evaluation method of resin composition> <Weather resistance test> Each resin composition (Formulation A and Formulation B) was applied to a Teflon (registered trademark) sheet at room temperature (25°C), and cured at 23°C and 50% RH for 6 days, and then at 50°C for 1 day in a saturated water vapor atmosphere to produce a 2 mm thick cured sheet (cured product). The resulting 2 mm thick cured sheet was placed in a metal weather meter (manufactured by Daipla Wintes, product name "METALWEATHER, model: KU-R5NCI-A") and measured at a temperature of 63°C, 70% RH, and illuminance of 80 mW / cm. 2 An accelerated weathering test was conducted under the condition that a two-minute shower was conducted once every two hours. The time at which abnormalities such as cracks began to appear in the appearance due to this accelerated weathering test (time to crack appearance) was recorded.
[0134] 1. Polymer synthesis <Synthesis of polyoxyalkylene polymer having crosslinkable functional group> Zinc hexacyanocobaltate glyme complex (0.05 g), polypropylene glycol (Mn: 2000, 50 g), and propylene glycol (510 g) were placed in a 1000 mL pressure-type stirred tank reactor equipped with an oil jacket, heated to 120 ° C, and reacted until the pressure change disappeared. Next, the mixture was heated under vacuum at 120 ° C for 1 hour to distill off the volatile components. Then, a 28% methanol solution of sodium methoxide (12.6 g) was added, and the pressure was reduced at 100 ° C for 1 hour to distill off the methanol. Next, allyl chloride (5.2 g) was added, and the mixture was heated at 100 ° C for 2 hours. Then, the reaction solution was washed twice with water (300 ml) to remove the salt. After dehydration by vacuum heating at 100°C for 2 hours, chloroplatinic acid hexahydrate (0.02g) and methyldimethoxysilane (8.3g) were added and reacted for 4 hours to obtain a polypropylene glycol both ends silylated (hereinafter also referred to as "polyoxyalkylene polymer X"). The molecular weight of polyoxyalkylene polymer X was Mn 22,900 and Mw 25,200 as determined by GPC measurement (polystyrene equivalent).
[0135] <Synthesis of (meth)acrylic polymer> <Production of polymer block (A)> (Synthesis Example 1: Production of polymer a-1) In a 250 mL flask equipped with a stirrer and a thermometer, RAFT agents were charged as follows: S,S-dibenzyl trithiocarbonate (hereinafter, also referred to as "DBTTC") (7.0 g), 2,2'-azobis(2-methylbutyronitrile) (hereinafter, also referred to as "ABN-E") (0.46 g), n-butyl acrylate (hereinafter, also referred to as "nBA") (62 g), ethyl acrylate (hereinafter, also referred to as "EA") (4 g), tetradecyl acrylate (hereinafter, also referred to as "TDA") (16 g), trimethoxysilylpropyl methacrylate (18 g), and trimethyl orthoacetate (hereinafter, also referred to as "MOA") (5.2 g). The mixture was thoroughly degassed by nitrogen bubbling, and polymerization was initiated in a thermostatic bath at 60°C. After 7 hours, the mixture was cooled to room temperature to stop the reaction. The molecular weight of the obtained polymer a-1 was Mn 4,200, Mw 6,700, and Mw / Mn 1.60 by GPC measurement (polystyrene equivalent). The reaction rates of each monomer measured by gas chromatography (GC) were nBA: 90%, EA: 92%, TDA: 91%, and trimethoxysilylpropyl methacrylate: 100%.
[0136] (Synthesis Examples 2 to 7, Comparative Synthesis Example 1: Production of Polymers a-2 to a-7, and a-9) Polymers a-2 to a-7 and a-9 were obtained in the same manner as in Synthesis Example 1, except that the raw materials used were as shown in Table 2. The molecular weight of each polymer and the reaction rate of each monomer were measured and are shown in Table 2.
[0137] (Synthesis Example 8: Production of polymer a-8) The raw materials were charged as shown in Table 2, and the polymerization was carried out at 58° C. for 2 hours, then the temperature was raised to 70° C. over 1 hour, and then the polymerization was carried out at 70° C. for 4 hours, and the same operation as in Synthesis Example 1 was carried out to obtain Polymer a-8. The molecular weight of the polymer and the reaction rate of each monomer were measured and are shown in Table 2.
[0138] [Table 2]
[0139] In Table 2, details of the compounds other than those described in Synthesis Example 1 are as follows. MMA: Methyl methacrylate
[0140] <Production of triblock copolymer> (Synthesis Example 9: Production of triblock copolymer b-1) In a 250 mL flask equipped with a stirrer and a thermometer, the polymer a-1 (6.2 g) obtained in Synthesis Example 1, nBA (71 g), EA (5 g), TDA (19 g), ABN-E (0.06 g), MOA (5 g) and ethyl acetate (20 g) were charged, thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 60 ° C. After 7 hours, the reaction was stopped by cooling to room temperature. The molecular weight of the obtained triblock copolymer b-1 was Mn 71,100, Mw 94,600, and Mw / Mn 1.33 by GPC measurement (polystyrene equivalent). In addition, the reaction rate of each monomer measured by gas chromatography (GC) was nBA: 89%, EA: 92%, and TDA: 90%.
[0141] (Synthesis Examples 10 to 19, Comparative Synthesis Examples 2 to 3: Production of triblock copolymers b-2 to b-11, b-13, and b-14) Triblock copolymers b-2 to b-11, b-13, and b-14 were obtained by the same procedure as in Synthesis Example 9, except that the raw materials used were as shown in Table 3. The molecular weight of each triblock copolymer and the reaction rate of each monomer were measured and shown in Table 3.
[0142] (Synthesis Example 20: Production of triblock copolymer b-12) A 250 mL flask equipped with a stirrer and a thermometer was charged with polymer a-8 (2.7 g) obtained in Synthesis Example 8, nBA (23.7 g), EA (1.8 g), TDA (6.4 g), ABN-E (0.05 g) and ethyl acetate (18 g), and the mixture was thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 70 ° C. 30 minutes after the start of polymerization, a monomer mixture solution obtained by mixing nBA (47.3 g), EA (3.2 g) and TDA (12.6 g) with stirring, and polymer a-8 (8.2 g) obtained in Synthesis Example 8 were continuously fed into the flask over 4 hours. After the end of the continuous feeding, a mixed solution of ABN-E (0.03 g) and ethyl acetate (2 g) was fed, and the internal temperature was raised to 60 ° C. over 30 minutes. After 7 hours from the start of polymerization, the mixture was cooled to room temperature to stop the reaction. The molecular weight of the obtained triblock copolymer b-12 was Mn 69,000, Mw 113,900, and Mw / Mn 1.65 by GPC measurement (polystyrene equivalent). The reaction rates of each monomer measured by gas chromatography (GC) were nBA: 83%, EA: 89%, and TDA: 86%. The values of each monomer, polymer a-8, initiator, and solvent in the charged raw materials in Table 3 are the totals of the initial charge amount and the continuous supply amount, respectively.
[0143] [Table 3]
[0144] <Production of Pentablock Copolymer> (Synthesis Example 21: Preparation of Pentablock Copolymer c-1) In a 250 mL flask equipped with a stirrer and a thermometer, the triblock copolymer b-1 (124 g) obtained in Synthesis Example 9, trimethoxysilylpropyl methacrylate (1.0 g), ABN-E (0.037 g) and MOA (0.21 g) were charged, thoroughly degassed by nitrogen bubbling, and polymerization was started in a thermostatic bath at 60 ° C. After 7 hours, the reaction was stopped by cooling to room temperature to obtain a solution containing pentablock copolymer c-1. The molecular weight of the obtained pentablock copolymer c-1 was Mn 68,800, Mw 88,800, and Mw / Mn 1.29 by GPC measurement (polystyrene equivalent). In addition, the reaction rate of each monomer measured by gas chromatography (GC) was nBA: 78%, EA: 84%, TDA: 75%, and trimethoxysilylpropyl methacrylate: 98%. The pentablock copolymer c-1 has a polymer block (A) consisting of nBA, EA, TDA and trimethoxysilylpropyl methacrylate, and a polymer block (B) consisting of nBA, EA and TDA, and is a pentablock copolymer having a block structure of (A)-(B)-(A)-(B)-(A). From the reaction rate, the composition ratio (mass ratio) of the polymer block (A) and the acrylic polymer block (B) was (A) / (B) / (A) / (B) / (A)=2.4 / 43.7 / 7.8 / 43.7 / 2.4 (wt%), which means that (A) / (B) was ≒13 / 87 (wt%).
[0145] (Synthesis Examples 22 to 32, Comparative Synthesis Example 4: Production of Pentablock Copolymers c-2 to c-13) Pentablock copolymers c-2 to c-13 were obtained by the same procedure as in Synthesis Example 21, except that the raw materials used were as shown in Table 4. The molecular weight of each block copolymer, the reaction rate of each monomer, and the composition ratio of the polymer blocks are shown in Table 4.
[0146] [Table 4]
[0147] 2. Preparation of (meth)acrylic polymers by reaction of block copolymers having thiocarbonylthio groups with nucleophiles <Post-treatment process of pentablock copolymers c-1 to c-13 and triblock copolymer b-14> (Production Example 1: Production of triblock copolymer d-1) The solution (100 g) containing the pentablock copolymer c-1 obtained in Synthesis Example 21 was thoroughly degassed by nitrogen bubbling, and then n-propylamine (0.31 g, 5 molar equivalents relative to the thiocarbonylthio group of the pentablock copolymer c-1) was added, and the decomposition reaction of the thiocarbonyl group was started in a thermostatic bath at 40°C. After 5 hours, the reaction was stopped by cooling to room temperature, and a solution containing triblock copolymer d-1 was obtained. The obtained solution was vacuum-dried using an evaporator, and triblock copolymer d-1 was recovered. The obtained triblock copolymer d-1 is a triblock copolymer having a polymer block (A) consisting of nBA, EA, TDA, and trimethoxysilylpropyl methacrylate, and a polymer block (B) consisting of nBA, EA, and TDA, and has an (A)-(B)-(A) block structure. 1 From the H-NMR measurement, it was confirmed that the peak (4.8 ppm) of hydrogen bonded to the carbon adjacent to the thiocarbonylthio group observed in the pentablock copolymer c-1 disappeared in the triblock copolymer d-1, and peaks (3.3 ppm, 2.9 ppm) derived from the Michael adduct with the residual acrylate compound (terminal molecular structure represented by the above formula (1)) appeared. From this result, it can be said that the triblock copolymer d-1 is a Michael adduct of the thiol formed by decomposing the thiocarbonylthio group of the pentablock copolymer c-1 with n-propylamine and the residual acrylate compound contained in the pentablock copolymer c-1. The molecular weight of the triblock copolymer d-1 was Mn 40,100, Mw 54,900, and Mw / Mn 1.37. In addition, the number of crosslinkable functional groups per molecule contained in the polymer block (A) was calculated to be 3.0 on average from the amount of trimethoxysilylpropyl methacrylate introduced per RAFT agent.
[0148] (Production Examples 2 to 12, Comparative Production Example 1: Production of Triblock Copolymers d-2 to d-13) Triblock copolymers d-2 to d-13 were obtained by the same procedure as in Production Example 1, except that the raw materials were used as shown in Table 5. The number of crosslinkable functional groups per molecule contained in block (A) calculated from the molecular weight of each block copolymer and the amount of methyldimethoxysilylpropyl methacrylate introduced per RAFT agent is shown in Table 5.
[0149] (Comparative Production Example 2: Production of triblock copolymer b-14) The solution containing the triblock copolymer b-14 obtained in Comparative Synthesis Example 3 was vacuum-dried using an evaporator to recover the triblock copolymer b-14. The obtained triblock copolymer b-14 has a polymer block (A) consisting of nBA, EA, TDA and methyldimethoxysilylpropyl methacrylate, and a polymer block (B) consisting of nBA, EA and TDA, and is a triblock copolymer having a block structure of (A)-(B)-(A). This triblock copolymer has a thiocarbonylthio group in the polymer block (B). The molecular weight of the triblock copolymer b-14 was Mn 41,500, Mw 50,600, and Mw / Mn 1.22. In addition, the number of crosslinkable functional groups per molecule contained in the polymer block (A) was calculated to be 3.0 on average from the amount of methyldimethoxysilylpropyl methacrylate introduced per RAFT agent.
[0150] [Table 5]
[0151] 3. Preparation and Evaluation of Resin Compositions Example 1 The Tg, viscosity and APHA of the triblock copolymer d-1 obtained in Production Example 1 were measured. In addition, the triblock copolymer d-1 was used as the (meth)acrylic polymer of the base resin, and resin compositions (formulation A and formulation B) were prepared according to the formulation table in Table 1. In addition, using each prepared resin composition, a cured sheet (cured product) was produced according to the weather resistance test described above, and the weather resistance of the cured sheet was evaluated. The results are shown in Table 6. In Table 6, the TDA content represents the content (mass%) of tetradecyl acrylate in the block copolymer, and is a value calculated from the charged amount and the reaction rate of the monomer.
[0152] (Examples 2 to 12, Comparative Examples 1 to 2) The Tg, viscosity and APHA of the polymers d-2 to d-13 obtained in Production Examples 2 to 12 and Comparative Production Example 1, and the polymer b-14 obtained in Comparative Production Example 2 were measured. In addition, the triblock copolymers d-2 to d-13 and b-14 were used as the base resin, and resin compositions (formulations A and B) were prepared according to the above-mentioned recipe (Table 1), and cured sheets (cured products) were produced for each. In addition, the weather resistance of the produced cured sheets was evaluated. The results are shown in Table 6.
[0153] [Table 6]
[0154] 4. Evaluation Results The polymers d-1 to d-12 obtained in Examples 1 to 12 had low Tg, relatively low viscosity, and low APHA value. Furthermore, the cured sheets obtained using the resin compositions (formulations A and B) containing the polymers d-1 to d-12 had excellent weather resistance. Among these, when focusing on the structural units of the (meth)acrylic polymer, the case having a structural unit derived from TDA (a (meth)acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms) (Example 4) had better weather resistance than the case not having a structural unit derived from TDA (Example 7).
[0155] On the other hand, the polymer d-13 obtained in Comparative Example 1 had a high Tg, and the viscosity exceeded the upper limit of the viscometer used for the measurement, making it impossible to measure. For this reason, it was difficult to obtain a resin composition (blending A and blending B) containing a triblock copolymer. In addition, the polymer b-14 used in Comparative Example 2 had a high APHA value. Furthermore, the cured sheets obtained from the resin compositions (blending A and blending B) containing the polymer b-14 had a shorter time until abnormalities such as cracks began to appear, and were inferior in weather resistance, compared to the resin compositions obtained in Examples 1 to 12.
Claims
1. The glass transition temperature is −15° C. or lower, The monomer constituting the molecular chain contains an acrylate compound, At least one terminal structure in the molecular chain is a structure represented by the following formula (1): A (meth)acrylic polymer having a Hazen color number (APHA) of 600 or less. 【Chemistry 1】 (In formula (1), R represents a residue obtained by removing an acryloyloxy group from an acrylic ester compound contained in the monomer that constitutes the molecular chain.)
2. The (meth)acrylic polymer according to claim 1 , which has a crosslinkable functional group.
3. The (meth)acrylic polymer according to claim 1 or 2, which is a block copolymer having two or more polymer blocks.
4. The (meth)acrylic polymer according to any one of claims 1 to 3, comprising a structural unit derived from a (meth)acrylic acid alkyl ester compound having an alkyl group having 10 or more carbon atoms.
5. The (meth)acrylic polymer according to any one of claims 1 to 4, having a molecular weight distribution (Mw / Mn) of 2.5 or less.
6. A resin composition comprising the (meth)acrylic polymer according to any one of claims 1 to 5.
7. The resin composition according to claim 6, further comprising a polyoxyalkylene polymer having a crosslinkable functional group.
8. The resin composition according to claim 6 or 7, which is for use as a sealant, an adhesive, a pressure sensitive adhesive or a coating material.
9. a step of polymerizing a vinyl monomer including an acrylic ester compound by a reversible addition-fragmentation chain transfer living radical polymerization method to produce a (meth)acrylic polymer (P1) having a thiocarbonylthio group; a step of reacting a thiocarbonylthio group of the (meth)acrylic polymer (P1) with a nucleophilic agent to produce a (meth)acrylic polymer (P2); Including, The (meth)acrylic polymer (P2) is The glass transition temperature is −15° C. or lower, The monomer constituting the molecular chain contains an acrylate compound, At least one terminal structure in the molecular chain is a structure represented by the following formula (1): The Hazen color scale (APHA) is 600 or less. A method for producing a (meth)acrylic polymer. 【Chemistry 2】 (In formula (1), R represents a residue obtained by removing an acryloyloxy group from an acrylic ester compound contained in the monomer that constitutes the molecular chain.)
10. The method for producing a (meth)acrylic polymer according to claim 9 , wherein the (meth)acrylic polymer (P2) is a block copolymer having two or more polymer blocks.
Citation Information
Patent Citations
Method for producing polymer
JP2017197649A
Thiocarbonylthio-free raft polymer and method of making same
JP2018522999A
Method for producing polymer
JP2019112591A
Novel chain transfer agent and emulsion polymerization using same
WO2011093401A1
Curable resin composition, block copolymer and method for producing same
WO2019208386A1